2010
DOI: 10.1073/pnas.0909400107
|View full text |Cite
|
Sign up to set email alerts
|

An organellar maturase associates with multiple group II introns

Abstract: Bacterial group II introns encode maturase proteins required for splicing. In organelles of photosynthetic land plants, most of the group II introns have lost the reading frames for maturases. Here, we show that the plastidial maturase MatK not only interacts with its encoding intron within trnK-UUU, but also with six additional group II introns, all belonging to intron subclass IIA. Mapping analyses of RNA binding sites revealed MatK to recognize multiple regions within the trnK intron. Organellar group II in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
209
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(213 citation statements)
references
References 41 publications
4
209
0
Order By: Relevance
“…THA8 is required for ycf3-2 splicing and strongly enhances trnA splicing. THA8 promotes trnA splicing in conjunction with the nucleus-encoded proteins WTF1 and RNC1, and, most likely, with the chloroplast gene product MatK (Zoschke et al 2010). THA8 is also the third nucleus-encoded splicing factor discovered for ycf3-2, following OTP51 (Falcon de Longevialle et al 2008) and APO1, a member of a plant-specific protein family with a novel zinc-dependent RNA-binding domain (Watkins et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THA8 is required for ycf3-2 splicing and strongly enhances trnA splicing. THA8 promotes trnA splicing in conjunction with the nucleus-encoded proteins WTF1 and RNC1, and, most likely, with the chloroplast gene product MatK (Zoschke et al 2010). THA8 is also the third nucleus-encoded splicing factor discovered for ycf3-2, following OTP51 (Falcon de Longevialle et al 2008) and APO1, a member of a plant-specific protein family with a novel zinc-dependent RNA-binding domain (Watkins et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…S2B). The MatK protein encoded in the trnK intron associates with all chloroplast subgroup IIA introns and is likely to be required for their splicing (Zoschke et al 2010). This information is summarized (Jenkins et al 1997;Vogel et al 1999;Jenkins and Barkan 2001;Till et al 2001;Ostheimer et al 2003;Barkan 2006, 2007;Schmitz-Linneweber et al 2006;Watkins et al 2007;Asakura et al 2008;Beick et al 2008;Falcon de Longevialle et al 2008;Prikryl et al 2008;Kroeger et al 2009;Chateigner-Boutin et al 2011;Watkins et al 2011).…”
Section: Plant Growthmentioning
confidence: 99%
“…Experimental data are lacking for the Arabidopsis orthologs of CRS2, PPR4, WTF1, RNC1, and PPR5, so the set of splicing factors shown for introns found in Arabidopsis but not maize (clpP-1, clpP-2, and rpoC1) is likely to be incomplete. The chloroplast-encoded protein MatK associates in vivo with all of the subgroup IIA introns except for clpP-int2 (Zoschke et al, 2010) and is anticipated to be required for the splicing of its intron ligands. The ndhA and ndhB introns are not designated as APO1 ligands because the splicing defects in apo1 mutants were mild.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…This indicates that an additional component, such as a helper protein, is required for splicing; however, none of the angiosperm organellar introns encodes an intronic ORF for splicing, except two (MAT-R encoded within nad1 intron 4 in mitochondria and MatK encoded within trnK in chloroplasts), and no such ORF is encoded alone in the organellar genome 6 . Recently, a report suggested that MatK associates with some group II introns in tobacco chloroplasts 83 . Nevertheless, nucleus-encoded machinery must be imported into both mitochondria and chloroplasts to help splicing.…”
Section: Post-transcriptional Regulation In Plant Mitochondria-encodementioning
confidence: 99%